Tourism sector and regional own-source revenue: A panel data analysis of six provinces in Java Island, Indonesia - Wirawan, Hanan Afif; El Hasanah, Lak lak Nazhat (Journal of Economics Research and Policy Studies, 2025)
This study aimed to analyze the influence of the tourism sector on Regional Original Revenue (PAD) in six provinces on Java Island from 2019 to 2023. The independent variables included the number of hotels, the number of restaurants, and the number of tourism workers, while the dependent variable was Regional Original Revenue (PAD). A quantitative approach was applied using panel data regression. Based on the Chow and Hausman tests, the Fixed Effect Model was selected as the most appropriate. The results showed that the number of hotels had a negative and significant effect on regional revenue, while the number of restaurants had no significant effect. Conversely, the number of tourism workers had a positive and significant impact. These findings indicated that hotels without effective management and optimal occupancy levels may hinder their contribution to regional income. At the same time, the tourism labor sector played a key role in enhancing revenue. This study offered strategic input for local governments in formulating sustainable tourism development policies aimed at strengthening regional income.